2018
DOI: 10.1371/journal.pone.0193578
|View full text |Cite
|
Sign up to set email alerts
|

Maternal DNA lineages at the gate of Europe in the 10th century AD

Abstract: Given the paucity of archaeogenetic data available for medieval European populations in comparison to other historical periods, the genetic landscape of this age appears as a puzzle of dispersed, small, known pieces. In particular, Southeastern Europe has been scarcely investigated to date. In this paper, we report the study of mitochondrial DNA in 10th century AD human samples from Capidava necropolis, located in Dobruja (Southeastern Romania, Southeastern Europe). This geographical region is particularly int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 58 publications
(53 reference statements)
2
22
0
Order By: Relevance
“…The analysis and interpretation of genome-wide aDNA data from more than 200 individuals inhabiting southeastern Europe between 12,000 and 500 BC, showed that this geographical region “served as a genetic contact zone between east and west over thousands of years 6 ”. This pattern was also observed in a small medieval group of individuals from southeastern Romania (Dobruja) 7 . The genetic connections to Central Asia were reflected by the presence of the N9a haplotype in 2 out of 10 successfully analyzed samples 7 .…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…The analysis and interpretation of genome-wide aDNA data from more than 200 individuals inhabiting southeastern Europe between 12,000 and 500 BC, showed that this geographical region “served as a genetic contact zone between east and west over thousands of years 6 ”. This pattern was also observed in a small medieval group of individuals from southeastern Romania (Dobruja) 7 . The genetic connections to Central Asia were reflected by the presence of the N9a haplotype in 2 out of 10 successfully analyzed samples 7 .…”
Section: Introductionsupporting
confidence: 65%
“…This pattern was also observed in a small medieval group of individuals from southeastern Romania (Dobruja) 7 . The genetic connections to Central Asia were reflected by the presence of the N9a haplotype in 2 out of 10 successfully analyzed samples 7 . Evidence from present-day maternal haplogroup diversity in the historical provinces of Romania showed that the Asian influence in Dobruja is greater than in the other regions, and suggested that the Carpathian Arch might have had an influential role in migration patterns 8 .…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…PCA based on haplogroup frequencies was conducted employing the function fviz_pca_biplot from the library factoextra [19] in R 3.4.0 [20]. The haplogroups frequencies of complete mitochondrial genomes from ancient populations (from Neolithic to medieval times) were taken from [21][22][23][24][25][26][27][28][29][30][31][32]. For a comparison with modern European variation, we used the data published by ref.…”
Section: Mitochondrial Haplogroup Definition and Population Genetics mentioning
confidence: 99%